Factors Associated with Hospital Profitability: A Systematic Review - Dafrossa Vony Silla; Ernawaty Ernawaty (Universitas Malahayati, 2026)
ABSTRACT Maximizing profitability is a goal that is often a challenge as healthcare providers work to balance the cost of providing effective, timely care and innovative services. This research aims to review the evidence that identifies the factors that can affect hospital profitability using a systematic review study. Articles published in the last 10 years in Proquest, Google Scholar, and EBSCO databases were systematically reviewed. Thirteen articles that met the inclusion and exclusion criteria were selected for further review. Findings regarding factors that can affect hospital profitabilitywere systematically synthesized. Thirteen articles explore This paper attempts to summarize the hospital profitability model by establishing relationships between the seventeen factors divided into six key subheadings identified such as organizational factors, managerial factors, patient mix factors, market conditions, health system and technology services. An examination of the factors was associated with hospital profitability and their impact on profitability can improve our understanding of the hospital industry. Further examination of the varying relationship between hospital operating factors and their profitability by hospital ownership type reveals that nonprofit hospitals behave very differently. Keywords: Hospital, Profitability, Systematic Review.